Evaluation of intra-fractional CBCT image quality using different megavoltage beam sizes and imaging conditions in a phantom study - Ruining Song; Shumin Cui; Baomin Chen (Scientific Reports)
Abstract The intra-fractional cone beam computed tomography can provide real-time anatomical information while saving treatment time, leading to important breakthroughs in image-guided radiation therapy. However, MV-level photon scattering during the image acquisition will disrupt the image quality. We obtained intra-fractional cone beam computed tomography images of a standard phantom using different sizes of MV-beam and imaging conditions such as imaging time, tube current and tube voltage. We analyzed the uniformity index, noise power spectrum, low contrast visibility and spatial resolution of the images to investigate the effect of MV-level photon scattering on the image quality of intra-fractional cone beam computed tomography. It was found that these parameters of the images varied regularly with the size of the MV-beam, which can help us to predict in advance whether the quality of the images meets the clinical requirements based on the radiation treatment plan to decide whether to use intra-fractional cone beam computed tomography. The research also shows that the different imaging conditions can improve or deteriorate the image parameter, which can also help us choose reasonable imaging conditions to obtain better image quality according to the clinical situation.